2011
DOI: 10.1136/gut.2010.233718
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 polyunsaturated fatty acids for the treatment and prevention of colorectal cancer

Abstract: Omega (u)-3 polyunsaturated fatty acids (PUFAs) are naturally occurring substances that are well tolerated and have been used extensively for the prevention of cardiovascular disease. More recently, u-3 PUFAs have been recognised to have anticancer activity. There is also evidence suggesting improved efficacy and/or tolerability of conventional cancer chemotherapy when administered with u-3 PUFAs. The purpose of this review is to (i) describe the mechanisms by which u-3 PUFAs are thought to have antineoplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
242
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(259 citation statements)
references
References 130 publications
12
242
2
3
Order By: Relevance
“…This finding reinforces the idea that omega-3 has immunomodulating effects in inflammation and healing, by stimulating cellular activity, and corroborates the findings of McDaniel et al 21 , who observed an inflammatory infiltrate increase of human healing skin wounds, as well as a significantly higher level of interleukin 1â (IL-1 â) in the inflammatory lesion fluid in the group that received the administration of EPA and DHA. This finding may seem conflicting with that proposed in the literature, that the omega-3 fatty acids have less pro-inflammatory activity by replacing arachidonic acid (omega-6 fatty acid) in the cell membrane and increase, through its metabolism, the production of eicosanoids of lower inflammatory potential, such as leukotriene B 5 and prostaglandin E 3 10,22 . Authors speculate that this increased cellular activity of the anastomotic environment is due to specific cell types, such as macrophages, fibroblasts, and myofibroblasts.…”
Section: Results Results Results Resultscontrasting
confidence: 55%
“…This finding reinforces the idea that omega-3 has immunomodulating effects in inflammation and healing, by stimulating cellular activity, and corroborates the findings of McDaniel et al 21 , who observed an inflammatory infiltrate increase of human healing skin wounds, as well as a significantly higher level of interleukin 1â (IL-1 â) in the inflammatory lesion fluid in the group that received the administration of EPA and DHA. This finding may seem conflicting with that proposed in the literature, that the omega-3 fatty acids have less pro-inflammatory activity by replacing arachidonic acid (omega-6 fatty acid) in the cell membrane and increase, through its metabolism, the production of eicosanoids of lower inflammatory potential, such as leukotriene B 5 and prostaglandin E 3 10,22 . Authors speculate that this increased cellular activity of the anastomotic environment is due to specific cell types, such as macrophages, fibroblasts, and myofibroblasts.…”
Section: Results Results Results Resultscontrasting
confidence: 55%
“…For example, g-tocopherol could be used as vitamin E in lipid emulsion because it has been reported, in contrast to a-tocopherol, to induce growth reduction and apoptosis in different colorectal cancer cell lines, including HT-29 cells [27]. It has been reported that the modulating effect of u-3 PUFAs on proinflammatory prostaglandin synthesis from COX-2 could play a role in minimizing side effects and increasing the efficacy of conventional radio-/chemotherapies [28]. We further speculate that u-3 PUFA peroxidation may play a significant role in cancer treatment, especially because cancer cells have been described to be more sensitive to oxidative stress than normal cells because of altered protecting mechanisms against free radical and reactive oxygen species [29].…”
Section: Discussionmentioning
confidence: 99%
“…Increased membrane fluidity, elevated unsaturation index, enhanced transport capabilities or enhanced oxidative stress caused by DHA can improve the uptake, intracellular distribution, and effects of chemotherapeutic drugs. This results in increased sensitivity to chemotherapy, especially in resistant tumour cells, and causes selective enhancement of cytotoxicity to tumour cells and protection of normal cells 120 . Paclitaxel, a taxane diterpenoid, is one of the most common anticancer drugs for the treatment of various types of solid tumours.…”
Section: Potentiation Of Anticancer Chemotherapeutic Drug Effects By Dhamentioning
confidence: 99%